Pre-reduction of Divrigi pellets with lignite and melting of pre-reduced pellets in a DC-EAF - Saridede, MN; Çizmecioglu, Z (METALLURGICAL SOC-C I M, 2003)
The scarcity of scrap is a serious problem in the iron and steel industry, especially in Turkey. Based on this problem, in this study the production of prereduced pellets (direct reduced iron-DRI) by using Turkish raw material sources and DRI usage in an electric arc furnace (EAF) was investigated. Effective parameters in reduction and melting experiments were studied. The experimental studies contained two parts. In the first part, Divrigi pellets were reduced by using Soma lignite in a laboratory type rotary kiln. In the reduction experiments, the variables were reduction time, temperature and ratio of C-f/Fe. At the end of the reduction experiments, it was revealed that by raising the temperature, time and Cf/Fe ratio, the metallization degree increases. In the kinetic investigation at the beginning of a reduction, the metallization degree is controlled by chemical reaction and after a period of time by diffusion mechanism. In the second part, the use of prereduced iron in the EAF was studied by a laboratory scale DC-EAF. The residual element content of produced steel decreased by increasing the prereduced iron content in the charge. In addition, the slag/metal distribution ratio increased with an increasing prereduced iron content.
Keywords: IRON-ORE FINES; ISOTHERMAL REDUCTION; KINETICS; CARBON; COAL; OXIDE; Metallurgy & Metallurgical Engineering